Arm slot angles affect elbow and shoulder joint torque in elite college pitchers - Dong, M.; Li, M.; Qu, Q.; Kim, Y.; Kim, S. (Sports Biomechanics, 2025)
The arm slot (AS) angle reflects the pitching style of baseball pitchers. Baseball pitchers at different levels exhibit different AS angle distributions and different pitching mechanics. The present study divided 66 elite baseball pitchers from the Open Biomechanics database into 3 groups based on AS angles: ASMi, ASMo, ASMa. The purpose of this study was to compare 30 kinematic and 10 kinetic differences between elite college baseball pitchers with different AS angles (reflective of pitching style) during pitching and to investigate the relationship between AS angle and selected shoulder and elbow kinetic parameters. The results of the study showed that the ASMa (67.31 ± 6.88°) had less trunk forward flexion and contralateral tilt at BR. Additionally, ASMa had significantly less elbow varus torque, greater elbow varus torque efficiency and shoulder internal rotation torque efficiency compared to the ASMi. AS angle had a significant negative correlation with elbow varus torque and a significant positive correlation with elbow varus torque and shoulder internal rotation torque efficiency, with an increase in elbow varus torque of approximately 4.23 N for every 10° increase in AS angles. AS angles associated with pitching style affect shoulder and elbow joint loading and corresponding biomechanical efficiency in elite college pitchers.